2016
DOI: 10.3892/br.2016.656
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic expression of DEC2 protein in vitro and in vivo

Abstract: Basic helix-loop-helix (bHLH) transcription factor DEC2 (bHLHE41/Sharp1) is one of the clock genes that show a circadian rhythm in various tissues. DEC2 regulates differentiation, sleep length, tumor cell invasion and apoptosis. Although studies have been conducted on the rhythmic expression of DEC2 mRNA in various tissues, the precise molecular mechanism of DEC2 expression is poorly understood. In the present study, we examined whether DEC2 protein had a rhythmic expression. Western blot analysis for DEC2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…DEC2 is more strongly expressed in thyroid cancer cells and carcinoma cells of osteosarcoma than in non-cancerous cells, but weakly expressed in gastric and pancreatic cancer cells [ 4 , 9 , 10 , 11 ]. We showed that DEC2 has circadian expression in tumor cells, such as in mouse sarcoma and in human hepatocellular carcinoma, osteosarcoma and breast cancer cells [ 12 , 13 , 14 ]. We have also shown that DEC1 and DEC2 play important roles in the regulation of apoptosis in human breast and oral cancer [ 1 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…DEC2 is more strongly expressed in thyroid cancer cells and carcinoma cells of osteosarcoma than in non-cancerous cells, but weakly expressed in gastric and pancreatic cancer cells [ 4 , 9 , 10 , 11 ]. We showed that DEC2 has circadian expression in tumor cells, such as in mouse sarcoma and in human hepatocellular carcinoma, osteosarcoma and breast cancer cells [ 12 , 13 , 14 ]. We have also shown that DEC1 and DEC2 play important roles in the regulation of apoptosis in human breast and oral cancer [ 1 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…By using rat-1 fibroblasts, Hirota et al demonstrated that glucose down-regulates the transcription of the Per1 and Per2 genes [ 98 ]. We and others have also reported that in cultured cells, Dec1 expression is increased by glucose supplementation, while glucose depletion decreases both DEC1 and DEC2 protein levels [ 43 , 99 ]. These findings are consistent with in vivo studies that fasting decreases and re-feeding increases Dec1 expression in the murine liver [ 68 , 69 , 70 ].…”
Section: Molecules At the Intersection Of The Molecular Clock And mentioning
confidence: 96%
“…First, Dec1 knockout mice decreased lipid levels and oxidative stresses, increasing fibroblast growth factor 21 (FGF21) levels [ 42 ]. Second, we revealed dominant energy sensor phosphorylation AMP-activated protein kinase (pAMPK), which mention at later Section 6 , is markedly increased in Dec2 knockout mice livers [ 43 ]. These evidences suggest that Dec play important roles in the regulation of circadian rhythm and metabolism.…”
Section: The Diurnal Rhythm Of Energy Metabolism and Its Significamentioning
confidence: 99%
See 2 more Smart Citations